giúp đi mà mn oie……………….

Question

giúp đi mà mn oie……………….
giup-di-ma-mn-oie

in progress 0
Latifah 1 year 2020-10-14T01:56:10+00:00 2 Answers 108 views 0

Answers ( )

    0
    2020-10-14T01:57:20+00:00

    2) $5x(2 – x) – 2 + x = 0$

    $\Leftrightarrow (2-x)(5x -1) = 0$

    $\Leftrightarrow \left[\begin{array}{l}2 – x = 0\\5x -1 = 0\end{array}\right.$

    $\Leftrightarrow \left[\begin{array}{l} x = 2\\x = \dfrac{1}{5}\end{array}\right.$

    4) $x^2(2x -3) + 12 – 8x = 0$

    $\Leftrightarrow x^2(2x – 3) – 4(2x -3) = 0$

    $\Leftrightarrow (2x -3)(x^2 – 4) = 0$

    $\Leftrightarrow (2x – 3)(x-2)(x +2) = 0$

    $\Leftrightarrow \left[\begin{array}{l}2x -3 = 0\\x -2 = 0\\x +2 = 0\end{array}\right.$

    $\Leftrightarrow \left[\begin{array}{l}x= \dfrac{3}{2}\\x =2\\x= -2\end{array}\right.$

    6) $x^3 +3x^2 +3x +1 = 8x^3$

    $\Leftrightarrow (x +1)^3 = (2x)^3$

    $\Leftrightarrow x + 1 = 2x$

    $\Leftrightarrow x = 1$

    8) $x^3 + 2x^2 = -x$

    $\Leftrightarrow x(x^2 + 2x +1) = 0$

    $\Leftrightarrow x(x +1)^2 = 0$

    $\Leftrightarrow \left[\begin{array}{l}x = 0\\x + 1 = 0\end{array}\right.$

    $\Leftrightarrow \left[\begin{array}{l}x = 0\\x  = -1\end{array}\right.$

    0
    2020-10-14T01:57:58+00:00

    $2) 5x(2 – x) – 2 + x = 0$

    $⇔ 5x(2 – x) – (2 – x) = 0$

    $⇔ (2 – x)(5x – 1) = 0$

    $⇔ \left[ \begin{array}{l}2-x=0\\5x-1=0\end{array} \right.$

    $⇔ \left[ \begin{array}{l}x=2\\x=\frac{1}{5}\end{array} \right.$

    $4) x²(2x – 3) + 12 – 8x = 0$

    $⇔ x²(2x – 3) – (8x – 12) = 0$

    $⇔ x²(2x – 3) – 4(2x – 3) = 0$

    $⇔ (x² – 4)(2x – 3) = 0$

    $⇔ (x – 2)(x + 2)(2x – 3) = 0$

    $⇔\left[\begin{array}{ccc}x-2=0\\x+2=0\\2x-3=0\end{array}\right]$

    $⇔\left[\begin{array}{ccc}x=2\\x=-2\\x=\frac{3}{2}\end{array}\right]$

    $6) x³ + 3x² + 3x + 1 = 8x³$

    $⇔ 7x² – 3x² – 3x – 1 = 0$

    $⇔ (x – 1)(7x² + 4x + 1) = 0$

    $⇔ x – 1 = 0$

    $⇔ x = 1$

    Giải thích:

    Ta có: $7x² + 4x + 1 = 7x² + 4x + \frac{4}{7} + \frac{3}{7} = (x\sqrt{7} + \frac{2\sqrt{7}}{7})² + \frac{3}{7} > 0$ với mọi x => $7x² + 4x + 1 = 0$ là vô lý ( vô nghiệm )

    $8) x³ + 2x² = -x$

    $⇔ x³ + 2x² + x = 0$

    $⇔ x(x² + 2x + 1) = 0$

    $⇔ x(x + 1)² = 0

    $⇔\left[ \begin{array}{l}x=0\\x+1=0\end{array} \right.$

    $⇔\left[ \begin{array}{l}x=0\\x=-1\end{array} \right.$

     

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )